Struggle For Life Of The Major CharacterIn Guy Ritchie's Sherlock Holmes (2009):An Individual Psychological Approach - Widayat, Ilham; Dr. Abdillah Nugroho, M.Hum (2017)
bstract The objective of the study is to examine how struggle for life of the major character is reflected in Guy Ritchie's Sherlock Holmes based on individual psychological approach and the structural elements. The object of the research is the movie entitled Sherlock Holmes written by Guy Ritchie. The research is conducted by using qualitative method; the researcher uses two data sources, namely primary and secondary data source. The primary data is the movie Sherlock Holmes written by Guy Ritchie. The secondary data sources are the other sources related to the analysis manuscript. The method of the data collection is observation. The technique of data analysis is descriptive analysis. The result of the research is as follows. Firstly, the structural element of the movie presents a solid unity. Secondly, the individual psychological analysis shows that the struggle for life of Sherlock Holmes comes from his social interest and is supported by his inferiority feeling. It makes his strive to reach the superiority and power in emerging the struggle for life but his strives to superiority goes in wrong way. In the end, it can be concluded that the struggle for life can find happiness. Finally, Sherlock Holmes gets his struggle to get the answer of the mystery. Key words: Sherlock Holmes, Individual Psychology